Impact of Inflammatory Bowel Disease (IBD) and IBD Medications on Risk of Hyperlipidemia and in vitro Hepatic Lipogenic-Related Gene Expression: A Population-Based Cohort Study - Tien, Ni; Wu, Tien-Yuan; Lin, Cheng-Li; Wu, Chia-Jui; Hsu, Chung-Y; Fang, Yi-Jen; Lim, Yun-Ping (Frontiers in medicine, 2022)
Patients with inflammatory bowel disease (IBD) present a higher risk of developing cardiovascular diseases (CVDs) due to chronic inflammation, which plays an essential role in atherogenesis. Hyperlipidemia is another risk factor for CVDs; however, the association between IBD, IBD medications, and hyperlipidemia remains controversial. We conducted a nationwide, population-based, retrospective, cohort study to examine the effect of IBD and IBD medications on the risk of developing hyperlipidemia. The effects of IBD medications on the expression of lipogenesis-related hepatic genes were also evaluated. We obtained data from the Longitudinal Health Insurance Database of Taiwan from patients with new-onset IBD and a comparison cohort of patients without IBD. A Cox proportional hazards regression model was used to analyze the difference in the risk of developing hyperlipidemia between the two cohorts. We also examined the influence of IBD medications on the expression of lipogenesis-related hepatic genes. After adjusting for comorbidities and confounding factors, the case group ( N = 14,524) had a higher risk for hyperlipidemia than the control group ( N = 14,524) [adjusted hazards ratio (aHR), 2.18]. Patients with IBD that did not receive IBD medications exhibited a significantly higher risk of hyperlipidemia (aHR, 2.20). In those treated with IBD medications, the risk of developing hyperlipidemia was significantly lowered than those without such medications (all aHR ≤ 0.45). Gene expression analysis indicated that IBD medications downregulated the expression of lipogenesis-related genes. Screening blood lipids in IBD patients is needed to explore the specific role and impact of IBD medications in the development of CVD.